Synthesis and in vitro evaluation of dioxopyrrolopyrroles as potential low-affinity fluorescent Ca2+ indicators - Nesibe Avcıbaşi; Mario Smet; Bert Metten; Wim Dehaen; Frans C. De Schryver; Geert Bultynck; Geert Callewaert; Humbert De Smedt; Ludwig Missiaen; Noël Boens (International Journal of Photoenergy)
Three new low-affinity fluorescent Ca2+ indicators excitable with visible light, namely 3-phenyl-6-(4-(3-carboxymethoxy-4-(N,N-dicarboxymethylamino)phenyl)phenyl)-2,5-dicarboxymethyl-1,4- dihydropyrrolo[3,4-c]pyrrole-1,4-dione (DPP1), 3-phenyl-6-(5-(3-carboxymethoxy-4-(N,N-dicarboxymethylamino) phenyl)thien-2-yl)-2,5-dicarboxymethyl-1,4-dihydropyrrolo[3,4-c]pyrrole-1,4-dione (DPP2) and 3- (thien-2-yl)-6-(5-(3-carboxymethoxy-4-(N,N-dicarboxymethylamino)phenyl)thien-2-yl)-2,5-dicarboxymethyl- 1,4-dihydropyrrolo[3,4-c]pyrrole-1,4-dione (DPP3) have been synthesized and evaluated for their Ca2+ binding properties via fluorimetric titrations. The in vitro dissociation constant Kd measured at 21 ∘C in 100 mM KCl buffered solution, pH 7.05, for the Ca2+ –DPP1 complex is 10 μM; for Ca2+ –DPP2 and Ca2+ –DPP3 a Kd value of 20 μM is found. All three indicators form 1 : 1 complexes with Ca2+. The fluorescence quantum yields of the uncomplexed forms of DPP1, DPP2 and DPP3 are 1.2×10−2, 3.4×10−2 and 3.6×10−2, respectively. After binding to Ca2+ these values increase to 4.8×10−2, 5.0×10−2 and 5.1×10−2, respectively.